2016
DOI: 10.1097/md.0000000000002970
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation in the Human SORBS1 Gene is Associated With Blood Pressure Regulation and Age at Onset of Hypertension

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…A significant association between a polymorphism of the threonine/alanine amino acid substitution at codon 228 (Thr228Ala) of SORBS1 and insulin resistance, obesity, and type 2 diabetes was already detected in a prior case-control study [46]. Furthermore, a recent study found other genetic variants of Sorbs1 significantly associated with blood pressure and hypertension, providing also a possible correlation with insulin resistance [47]. …”
Section: Discussionmentioning
confidence: 91%
“…A significant association between a polymorphism of the threonine/alanine amino acid substitution at codon 228 (Thr228Ala) of SORBS1 and insulin resistance, obesity, and type 2 diabetes was already detected in a prior case-control study [46]. Furthermore, a recent study found other genetic variants of Sorbs1 significantly associated with blood pressure and hypertension, providing also a possible correlation with insulin resistance [47]. …”
Section: Discussionmentioning
confidence: 91%
“…The same phenomenon was observed to carry over generations from grandparents to grandchildren, though less robustly [60]. In addition to observed heritability patterns in population studies, specific genetic determinants have been identified for early onset hypertension in several studies [61][62][63][64][65].…”
Section: Age Of Hypertension Onsetmentioning
confidence: 84%
“…SORBS1 is an adaptor protein involved in insulin signalling. Polymorphisms in the SORBS1 gene have been associated with various, non-lung related, diseases,11 12 but its role in lung disease is unexplored. The new SORBS1 splice variant includes an additional exon encoding for an atrophin-1 domain.…”
Section: Resultsmentioning
confidence: 99%